Formulation consideration and characterization of microemulsion drug delivery system for transnasal administration of carbamazepine - Rashmin B. Patel; Mrunali R. Patel; Kashyap K. Bhatt; Bharat G. Patel (Faculty of Pharmacy, Cairo University, 2013)
The purpose of the present study was to formulate and characterize carbamazepine loaded microemulsion and mucoadhesive microemulsion drug delivery system for its intranasal administration. Carbamazepine microemulsion and mucoadhesive microemulsion were prepared by titration method. The drug-loaded microemulsions were successfully prepared which contain 6% Labrafil M 1944 CS as an oily phase, 32% surfactant mixture of Cremophor RH 40: Transcutol P (4:1) and 62% (wt/wt) aqueous phase. Microemulsion formulation which displayed an optical transparency of 99.95%, globule size of 34.32 ± 1.09 nm, and polydispersity index of 0.127 ± 0.012 was selected for the incorporation of mucoadhesive component. The drug-loaded mucoadhesive microemulsion that contains 0.5% wt/wt of polycarbophil displayed higher in vitro mucoadhesive potential (21.0 ± 3.0 min) and diffusion coefficient (0.3172 ± 0.03) than microemulsion. All formulations were found free from nasal ciliotoxicity and stable for 6 months.